In the wake of the Mongols the making of a new social order in North China, 1200-1600 - Wang, Jinping 1979- (Harvard-Yenching Institute monograph series, 2018)
"Recounts the riveting story of the Mongol conquest of north China, which inflicted terrible wartime destruction, and how the northern Chinese adapted to changed circumstances and interacted with their conquerors to create a drastically new social order. Delineates the region's changing social dynamics over four centuries of Mongol rule"--Provided by publisher.